New diatom species Diploneis zhui sp. nov. from Jiuzhaigou National Nature Reserve, China - SUN, GENG; LEVKOV, ZLATKO; XIAO, WEIYANG; MORAJ, NIKOLA; UDOVIČ, MARIJA GLIGORA; DU, JIE; CHEN, QUNLONG; PLENKOVIĆ-MORAJ, ANĐELKA (Magnolia Press, 2023)
Diploneis zhui sp. nov. was observed in epilitic diatom communities from Jiuzhaigou National Nature Reserve. The species is described herein based on light microscopy (LM) and scanning electron microscopy (SEM) and ecological information of the type locality is provided. The species is characterized by linear to linear-elliptic valves with broadly rounded ends, 18–39 μm long, and 9.5–11.0 μm wide and partly biseriate striae, 16–18 in 10 μm. The species is compared with most similar taxa from other regions. The discovery of a new diatom species confirms the importance of Jiuzhaigou not only in terms of species richness and endemicity, but also for the biodiversity of freshwater karst ecosystems.